Interplay between the human gut microbiome and host metabolism - Alessia Visconti (Nature Portfolio, 2019)
Here, the authors study the interplay between the microbiome and faecal and blood metabolome, and how the microbiome interacts in the dialogue between these metabolic compartments, identifying a key role for microbial functions and underscoring their relevance for microbiome therapeutic strategies.